2018
DOI: 10.1002/hpja.209
|View full text |Cite
|
Sign up to set email alerts
|

“It's like you are in the jungle”: Using the draw‐and‐tell method to explore preschool children's play preferences and factors that shape their active play

Abstract: Issue addressed A child's preference for active or sedentary play is a key proximal indicator of a child's physical activity behaviour. There is a need to understand children's physical activity preferences in order to make physical play more enjoyable to them, and this may encourage participation and a more positive relationship with physical activity. To date, little research has incorporated the perspectives of young children on this topic. This study specifically examines (a) what activities preschool chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Pre-school children's play preferences and the characteristics of these plays provide educators with important information. The findings will help to support children's participation in entertaining and creative activities in natural settings (Wiseman et al, 2018). Children prefer open-ended plays, which shows their desire for unconfigured plays.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Pre-school children's play preferences and the characteristics of these plays provide educators with important information. The findings will help to support children's participation in entertaining and creative activities in natural settings (Wiseman et al, 2018). Children prefer open-ended plays, which shows their desire for unconfigured plays.…”
Section: Discussionmentioning
confidence: 78%
“…Given the positive impact of outdoor plays on children's development, teachers are recommended to provide children with play opportunities in natural settings (Bento & Dias, 2017;Kemple et al, 2016;Miranda et al, 2017). In this context, placing more outdoor play materials and natural materials such as water and sand that children can use, will allow children to prefer outdoor plays more and participate in them (Miranda et al, 2017;Wiseman et al, 2018;Zamani, 2016)…”
Section: Playgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (for example Livingstone 2011;Hjarvard 2014) have continuously demonstrated the trend that children in urban Western societies are currently growing up in media-rich households where they are surrounded by a wide range of digital tools and devices. Previous studies using the draw-and-write/tell method (Marshall and Aitken 2006;Wiseman et al 2019) on studying children's favourite possessions and activities have described the rise of technology: for example, nearly one third of young New Zealanders aged 8-11 (n=84) drew electronic equipment (for example games console, TV, X-box, mobile phone, etc.) as their favourite possessions (Marshall and Aitken 2006).…”
Section: G I F T S a N D F Av O U R I T E T H I N G Smentioning
confidence: 99%
“…The studies adopt various methodologies exploring knowledge and behaviours with diverse populations in a range of settings. Nicola Wiseman, Christin Rossmann, Jessica Lee and Neil Harris explore the world of the pre‐school child through the innovative approach of drawing to determine their physical activity preferences. Judith Myers and colleagues report on the findings of a pilot intervention to improve nutrition and active play in young children (0‐4 years).…”
mentioning
confidence: 99%